Osseodensification - A novel approach in implant dentistry - Umesh Y Pai; Shobha J Rodrigues; Karishma S Talreja; Mahesh Mundathaje (Wolters Kluwer Medknow Publications, 2018)
Primary stability in dental implants is an essential factor for achieving successful osseointegration. Surgical procedure and bone quality are among the most common factors that affect primary stability. It is also crucial to achieve high-insertion torque which is important for obtaining primary stability. Maintaining sufficient bone bulk and density is essential to achieve necessary bone-to-implant contact for obtaining a biomechanically stable implant. A new concept for osteotomy called osseodensification (OD) has been at the forefront of changes in surgical site preparation in implantology. This relatively new concept with universally compatible drills has been proposed to help in better osteotomy preparation, bone densification, and indirect sinus lift and also achieve bone expansion at different sites of varying bone densities. This procedure has also shown improvement in achieving better implant primary stability and better osteotomy than conventional implant drills. A systematic review was undertaken to analyze if OD procedure had any advantages over conventional osteotomy on bone density and primary stability. An electronic database search was conducted in PubMed using keywords such as "OD," "implant primary stability," "implant bone density," and "implant osteotomy." A total of 195 articles were collected and subjected to screening using inclusion and exclusion criteria. A literature review was done, following which it was seen that the use of versah drills for bone OD resulted in undersized osteotomy compared to conventional drills. It also resulted in improved bone density and increase in percentage bone volume and bone-to-implant contact, thereby improving implant stability.